Application of alkyl sulfates and heat treated erythrocytes in hypertonic cryohemolysis - Шпакова, Н.М.; Єршова, Н.А.; Орлова, Н.В.; Єршов, С.С.; Синчикова, О.П. (Biotechologia Acta. – 2015. – Vol.8, №3. – P.126-136, 2015)
The research aim was to study the application efficiency of alkyl sulfates and heat treatment of erythrocytes of mammals (human, horse, bull and rabbit) in order to increase their resistance to hypertonic cryohemolysis. The hemolysis rate for erythrocytes was recorded by spectrophotometry; the efficiency of alkyl sulfates was assessed on the values of maximum antihemolytic activity and the ones of effective concentrations; mammalian erythrocytes were morphologically analyzed by light microscopy. It has been found that anionic amphiphiles (sodium decyl and dodecyl sulfates) exhibit an antihemolytic activity in hypertonic cryohemolysis of erythrocytes. There was shown the transformation of erythrocytes on the “discocyte-echinocyte” type in the presence of alkyl sulfates, indicating to the distribution of amphiphilic molecules in an outer monolayer of erythrocyte membrane bilayer. It has been revealed that pre-incubation of the cells at 49 C increases the resistance to hypertonic cryohemolysis effect for human and equine erythrocytes and as well as it reduces the one for bovine and rabbit cells. Sodium decyl and sodium dodecyl sulfates exhibit an antihemolytic activity under hypertonic cryohemolysis of heat treated mammalian erythrocytes, but it is lower if compared with the control cells. The findings about distribution of alkyl sulfates in membranes and their antihemolytic activity under conditions of hypertonic cryohemolysis of heat treated erythrocytes testify to the perspective of using these substances as the tool for assessing the state of erythrocyte membranes when changing the temperatureosmotic environment. -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Метою роботи було дослідження ефективності застосування алкілсульфатів і термообробки еритроцитів ссавців (людина, кінь, бик і кролик) з метою підвищення їхньої стійкості до дії гіпертонічного кріогемолізу. Рівень гемолізу еритроцитів реєстрували спектрофотометричним методом; ефективність алкілсульфатів оцінювали за величинами максимальної антигемолітичної активності та значеннями ефективних концентрацій; морфологічний аналіз еритроцитів здійснювали методом світлової мікроскопії. Встановлено, що аніонні амфіфіли (децилсульфат і додецилсульфат натрію) виявляють антигемолітичну активність за умов гіпертонічного кріогемолізу еритроцитів досліджуваних ссавців. Показано транс формацію еритроцитів за типом «дискоцит–ехіноцит» у присутності алкілсульфатів, яка свідчить про розподіл амфіфільних молекул у зовнішньому моношарі бішару еритроцитарної мембрани. Встановлено, що попереднє інкубування клітин при 49 С підвищує стійкість еритроцитів людини і коня до дії гіпертонічного кріогемолізу, однак знижує стійкість еритроцитів бика і кролика. Децилсульфат і додецилсульфат натрію виявляють антигемолітичну активність за умов гіпертонічного кріогемолізу термооброблених еритроцитів ссавців, проте вона нижча, ніж для контрольних клітин. Отримані дані щодо розподілу алкілсульфатів у мембрані та їхньої антигемолітичної активності за умов гіпертонічного кріогемолізу термооброблених еритроцитів свідчать про перспективу використання цих речовин як інструменту для оцінювання стану мембран еритроцитів за зміни температурно-осмотичних умов середо вища.
ВИКОРИСТАННЯ АЛКІЛСУЛЬФАТІВ І ТЕРМООБРОБКИ ЕРИТРОЦИТІВ ЗА ГІПЕРТОНІЧНОГО КРІОГЕМОЛІЗУ
Shpakova NM, Iershova NA, Orlova NV, Iershov SS, Synchykova OP. Application of alkyl sulfates and heat treated erythrocytes in hypertonic cryohemolysis. Biotechologia Acta. 2015; 8 (3):126-36
Keywords: кріогемоліз; амфіфільні речовини; температура; еритроцити ссавців; mammalian erythrocytes; alkyl sulfates; cryohemolysis; heat treatment; термообробка